Analysis of cutaneous adverse drug reactions in a tertiary care hospital in South Tamil Nadu - Murthy, Aravind Baskar; K., Amuthavalli; P., Nirmaladevi; B., Meenakshi (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Cutaneous adverse drug reactions (CADRs) are among the most frequently reported adverse drug reactions (10 to 30%) with overall incidence of 6.2/1000 cases in India and 8% of hospitalisation among Dermatology inpatients. The aim was to analyse the CADRs with reference to its prevalence, causative drugs, morphological patterns, polypharmacy and drug reaction severity by Hartwig’s severity assessment scale. Methods: This study was a retrospective study done in the Department of Dermatology, Venereology and Leprosy (DVL) over a period of 5 years (2015 to 2019) from CADR registers. Mean, standard deviation and chi square test were used for statistical analysis. P≤0.05 was considered as statistically significant. Results: A total of 134 cases of CADRs were encountered which comprised 0.2% (2/1000) of total OP census with equal gender ratio and involved most commonly the younger adults. The drug groups mainly responsible were anticonvulsants (24.7%) followed by non-steroidal anti-inflammatory drugs (NSAIDS) (22.5%), antibiotics (20.9%) followed by antiretrovirals (ART) and antituberculous drugs (ATT). The common morphological patterns were acute exanthem (32.2%), exfoliative dermatitis (14.9%) and toxic epidermal necrolysis (14.2%). Over the counter drugs accounted for 25.6% of cases. Around 38.1% were on polypharmacy. In this study, 15.7% had mild CADR, 53.7% had moderate and 30.6% had severe drug reactions with 2.2% mortality based on the Hartwig’s severity assessment scale. Commonest cause of severe CADRs was anticonvulsants and benign CADRs was NSAIDS. Conclusions: Proper history taking and documentation of data, recollection of sequence of events by the patient and drug re-challenge will help us in deciding the causative drug preventing further occurrence.